Energy Efficiency and Techno-Economic Analysis of a Thermochemical Energy Storage System by Using a Fluidized Bed Reactor Integrated with a Steam Rankine Cycle of a Biomass Power Plant - Yasui, Takahito; Aoki, Masahiro; Uchino, Takayuki; Fushimi, Chihiro (ACS Engineering Au, 2023)
A thermochemical heat storage system using Ca(OH)2/CaO in a fluidized bed reactor (FBR) is integrated with a biomass power plant of a steam Rankine cycle (SRC) as one of the Carnot battery systems that are expected to provide renewable electricity highly flexibly. This study utilizes the proposed fluidized bed model under the nonsteady state operation to evaluate the energy efficiency and cost by varying the fluidized bed configuration and the power generation capacities. In addition, the performances of the SRC and those of the organic Rankine cycle (ORC) were compared, and the fuel cost reduction by the biomass savings was considered. The levelized cost of storage (LCOS) of the SRC in the base case (6.25 MWe, bed volume = 100 m3, bed height/diameter ratio = 4, FBR inlet gas velocity = 0.087 m/s) was 0.804 and 0.197 USD/kWhe when the charging electricity cost was 0.100 and 0 USD/kWhe, respectively. The charging electricity cost has a dominant effect on the LCOS. The stored energy efficiency and the round-trip efficiency were 58.2 and 13.7% (without biomass saving), respectively, and the net power generation was 1247.3 MWhe/year. The effect of fluidized bed volume, bed height/diameter ratio, and power generation capacity of the SRC has a slight influence on the energy efficiency and LCOS. However, the gas velocity in the FBR has a substantial influence on the net energy generation and LCOS. In the case that power generation capacity is 3 MWe and the charging electricity cost is 0 USD/kWhe, the LCOS is 0.204 USD/kWhe (SRC) and 0.520 USD/kWhe (ORC), respectively, indicating that SRC has a cost advantage for a 3 MWe-class power plant. This is because SRC has higher power generation efficiencies (24.3%) than that of the ORC (11.4%), generating more electricity from the stored heat. The effect of biomass saving on LCOS was 0.026–0.053 USD/kWhe (SRC) and 0.096 USD/kWhe (ORC). Increase of power generation efficiency and/or effective utilization of exhaust heat from the turbine is important to increase energy efficiency and decrease LCOS.